La atención y la comprensión lectora de los estudiantes de quinto grado de la Escuela de Educación Básica Particular “Montessori”, 2023 – 2024. - Vasquez Sarmiento, Dayanna Elizabeth (2025)
The purpose of this study is to analyze the relationship between attention and reading comprehension among fifth-grade students at "Montessori" Private Basic Education School. The research was carried out using a quantitative, descriptive, correlational, and transversal approach, with a non-experimental design. A sample of 12 students was administered the Toulouse-Piéron Test to measure attention and the Progressive Linguistic Complexity Test (PLC) for reading comprehension. Statistical data processing was carried out using Excel, SPSS software, Kendall's Tau-b correlation coefficient, and Pearson's correlation coefficient interpretation table. The obtained results show a low level of attention, with 41.67% of students exhibiting impulsive response patterns, and in the case of reading comprehension, they achieved a low score of 66.67%. Finally, the inferential analysis showed a strong positive correlation, indicating that attention influences reading comprehension. Therefore, the alternative hypothesis that attention is significantly related to reading comprehension in fifth graders was accepted